Student-teacher dialogue for lesson planning: inclusion in the context of national policy and local culture - Lotte Hedegaard-Soerensen; Sine Penthin Grumloese (Taylor & Francis Group, 2020)
This paper reports on the findings of an Erasmus project entitled 'ReHaRe' (Reaching the Hard to Reach). The aim of this project is to develop more inclusive learning environments. The project adopts an action research approach and gives school pupils a role as researchers who plan, evaluate and develop lesson plans in collaboration with their teachers. The paper describes the way in which this collaboration can increase the degree to which pupils participate in the planning of their teaching, including pupils who are normally regarded as being hard to reach. However, this action research approach also generates ethical dilemmas, especially when children are at the centre of inquiry. Equal partnerships in research (in this case teacher-pupil equality) require reflection on the underlying ideas of the teacher-pupil relation and an awareness of how these ideas affect collaboration, especially when teachers insist on maintaining their dominant role over pupils. The paper concludes that inclusive inquiry - which was the approach taken in this project - can expand participatory opportunities for children who are otherwise regarded as being on the margins of the education system. However, successful inclusive research also requires an understanding of the role of local professional cultures at schools.